Safari Dakwah Berbasis Islam Mahasiswi KKN STIBA Makassar di Dusun Dasan Bagik, Lombok Timur - Sri Ujiana Putri; Dewi Indriani; Armida (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Dasan Bagik Village is a Muslim majority area that maintains Islam in the midst of existing religious diversity. This Islamic value is also passed down to the next generation. The purpose of implementing Community Service (KKN) is as a form of community service which is a pillar of the Tri Dharma of Higher Education. The method of implementing community service in Dasan Bagik Village begins with mapping the problems and needs of the community throught SOAR analysis. After the mapping is done, a work program is prepared in accordance with the needs of the local community. So the work programs that have been initiated are the teaching at Madrasah Tsanawiyah, teaching adult Al Quran (tahsin), daurah pra ta’rif and Sholeh Children Festival (FAS). The result of the implementation of this work program show that the general public is very enthusiastic. This is evident from the change in society after following some of the work programs above. Like muslim womenwho have begun to be able to read the Koran according the correct tajwid principles, the practice of discussing Arabic is active among students of Tsanawiyah madrasah, and children who are confident in displaying their abilities in public.